2016
DOI: 10.4103/2008-322x.180709
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography in retinal diseases

Abstract: Optical coherence tomography angiography (OCTA) is a new, non-invasive imaging system that generates volumetric data of retinal and choroidal layers. It has the ability to show both structural and blood flow information. Split-spectrum amplitude-decorrelation angiography (SSADA) algorithm (a vital component of OCTA software) helps to decrease the signal to noise ratio of flow detection thus enhancing visualization of retinal vasculature using motion contrast. Published studies describe potential efficacy for O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
169
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(180 citation statements)
references
References 42 publications
0
169
0
7
Order By: Relevance
“…It shows both structural and blood flow changes, and provides a highly detailed view of the retinal vasculature. 20 In our case, the OCTA showed an irregular enlargement of the foveal avascular zone, with loss of capillaries superiorly, in the internal and external retinal plexus.…”
Section: Discussionmentioning
confidence: 95%
“…It shows both structural and blood flow changes, and provides a highly detailed view of the retinal vasculature. 20 In our case, the OCTA showed an irregular enlargement of the foveal avascular zone, with loss of capillaries superiorly, in the internal and external retinal plexus.…”
Section: Discussionmentioning
confidence: 95%
“…OCTA provides a three-dimensional vascular mapping at the microcirculation level and has shown its ability to identify important vascular changes in different retinal and choroidal diseases including diabetic retinopathy, retinal vascular occlusions and choroidal neovasculartisation (CNV) 1 2…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, ultrafast ultrasound imaging has been demonstrated to provide depictions of choroidal flow dynamics, including velocities over the cardiac cycle [21]. These imaging techniques provide documented substantiation of increased choroidal perfusion [22]. Overall, these techniques show growing promise for even more precise measurements of choroidal perfusion in the future and should be developed further.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that sildenafil mediates choroidal flow by determining the fraction of the choroid occupied by measurable flow (decorrelation) using the swept-mode ultrasound imaging technique as a proxy for choroidal perfusion [21]. A similar processing scheme is currently used in split-spectrum OCT angiography to define the vascular density (the percentage area occupied by blood vessels) having at least two standard deviations above noise [22]. Most recently, ultrafast ultrasound imaging has been demonstrated to provide depictions of choroidal flow dynamics, including velocities over the cardiac cycle [21].…”
Section: Discussionmentioning
confidence: 99%